Gambaran Keterampilan Keperawatan Komunitas Di Puskesmas Getasan - Treesia Sujana; Agus Fitrianto; Dessy Febriyanti Hady (Jurnal Keperawatan Muhammadiyah, 2020)
Nurse skills are affecting their performance as a health worker.Â  The skills are clinical skills that can be applied in accordance with the needs of the community. This research aims to describe of community nursing skills at Getasan health center. The method the researcher used was descriptive. Data collection is done by in-depth interviews using interactive model techniques. Using these techniques the researcher can describe the phenomenon studied. The community nursing skills depicted from the research are: (1) the role of the community nurse are in providing community nursing care, educators, coordination, and collaboration; (2) community nursing skills which been used in the community comprises of : nurses carry out routine activities inside and outside the health center in the form of health promotion, preventive acts, Integrated development post, Integrated health post, elderly surveillance etc; (3) community nursing barriers which identified are : lack of human resources and the difficulty of changing people paradigm about the importance of health examination. Conclusion: implementations of nursing skills in the health centers are providing nursing care as an educators, coordinator, and collaborator; and the skills of community nursing in giving promotive and preventive actions